Challenge-based learning assisted by virtual reality STEAM trails at a cultural heritage museum to promote mathematical creative thinking skills - Winasis, Andy Nova; Rejeki, Asri; Cahyono, Adi Nur (Universitas Hamzanwadi, 2025)
The 21st century requires every individual to possess creative thinking skills to face increasingly complex challenges. This skill can be developed through learning mathematics. This study aimed to determine the quality of challenge-based learning assisted by virtual reality STEAM Trails in the context of the Pekalongan Batik Museum to improve mathematical creative thinking skills. The method used in this study was design research. The participants of this study were 30 ninth-grade students at a junior high school in Pekalongan, Indonesia. The data collection techniques included validation sheets, questionnaires, and tests. Qualitative data analysis techniques were used to analyse the students' responses after learning. Quantitative data analysis techniques were used to analyse mathematical creative thinking skills based on the pretest and posttest results. Validity was analysed based on the validation results by three validators, and practicality was analysed based on the results of the practicality questionnaire by five students from the experimental group. The results of this study showed a significant increase in the pre- and post-test results. Additionally, the results of the student response questionnaire indicated high satisfaction with the learning process. Further research is needed to develop VR for other contexts.